Morphometric study of Kalophrynus palmatissimus at two forest reserves in Malaysia - Abdul Aziz, Muhammad Faris; Mohd Top @ Mohd Tah, Marina; Shohaimi, Shamarina; Ab Ghani, Nurul Izza; Fletcher, Christine (Wiley Open Access, 2021)
A research study on morphometrics of Kalophrynus palmatissimus (commonly known as Lowland Grainy Frog) at Ayer Hitam Forest Reserve (AHFR), Selangor and Pasoh Forest Reserve (PFR), Negeri Sembilan was carried out from 12 November 2016 to 13 September 2017. The study was to examine data on the morphometric traits of K. palmatissimus at the two forest reserves. 15 morphometric traits of K. palmatissimus that were taken by using vernier calipers. Frog surveys were done by using 15 and 18 nocturnal 400 m transect lines with an interval distance of 20 m at AHFR and PFR, respectively. The GPS coordinates for all frog samples were recorded to ensure the precise geographic location. In addition, five climatic data were recorded. The results showed that most morphometric traits in AHFR (n = 34) and PFR (n = 31) were positively correlated with each other. On the other hand, climatic factor, which was soil pH, had a significant positive influence on most of the morphometric traits (p < .01), except for tympanum diameter and upper eyelid width (p ≥ .05). Meanwhile, the temperature had a significantly negative influence on all morphometric traits (p < .01). General linear model (GLM) analysis showed that snout-vent length (SVL) influenced most morphometric traits (F ≤ 80.86, p < .01), except for hand length (HAL: F = 0.299, p > .05). Later, it was found that the snout-vent length of K. palmatissimus at AHFR was slightly larger than at PFR (AHFR: μ = 37.00 mm, SE = 1.16 c.f. PFR: μ = 30.29 mm, SE = 1.07). It showed that there were variations in morphometric traits of K. palmatissimus at AHFR and PFR. From PCA analysis, morphometric traits are grouped into two components for AHFR and PFR, respectively. In AHFR, head length, eye diameter, head width, internarial distance, interorbital distance, forearm length, tibia length, foot length, and thigh length were strongly correlated, while snout length and eye-nostril distance were strongly correlated. In PFR, eye diameter, head width, internarial distance, interorbital distance, foot length, and thigh length were strongly correlated, though snout length and eye-nostril distance were strongly correlated, hence, suggested that all morphometric traits grow simultaneously in K. palmatissimus with eye-nostril distance (EN), and snout length (SL) growing almost simultaneously at AHFR (r = .91) and PFR (r = .97). There is still a lack of available information regarding the distribution and morphometric studies of K. palmatissimus in Malaysia, especially at AHFR and PFR. This study showed 15 different morphometric traits of K. palmatisssimus between AHFR and PFR, with K. palmatissimus at AHFR were found to be slightly larger than at PFR.